Research on the farmers’ agricultural digital service use behavior under the rural revitalization strategy—Based on the extended technology acceptance model - Wang, Bo; Dong, Hao (Frontiers in Environmental Science, 2023)
The effective use of agricultural digital services can promote the transformation of agricultural production methods and actively promote the development of agricultural economy. However, in the process of agricultural production and operation, farmers are difficult to use agricultural digital services and are still at a disadvantage in the use of information. The rapid development and promotion of agricultural digital services provide opportunities for farmers to cross the 'digital divide' and obtain 'data dividend'. Based on the extended technology acceptance model, this paper uses the partial least squares structural equation model to empirically analyze the key influencing factors of farmers ' agricultural digital service use behavior. The research shows that farmers' agricultural digital use behavior is mainly affected by two key factors: adoption intention and facility conditions. Among them, adoption intention has a more significant impact on use behavior. At the same time, adoption intention is affected by performance expectation, social influence and data quality, which is an important pre-factor affecting behavior attitude.